The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3748/wjg.15.3106
|View full text |Cite
|
Sign up to set email alerts
|

Constructive thinking, rational intelligence and irritable bowel syndrome

Abstract: AIM:To evaluate rational and experiential intelligence in irritable bowel syndrome (IBS) sufferers. METHODS:We recruited 100 subjects with IBS as per Rome Ⅱ criteria (50 consulters and 50 non-consulters) and 100 healthy controls, matched by age, sex and educational level. Cases and controls completed a clinical questionnaire (including symptom characteristics and medical consultation) and the following tests: rationalintelligence (Wechsler Adult Intelligence Scale, 3rd edition); experiential-intelligence (Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Patients in these studies were recruited from community advertising and research databases rather than gastroenterology clinic. A separate study that examined cognition in just IBS sufferers, found no difference in intelligence scores compared to healthy volunteers, but observed an association with a concept called constructive thinking which reflects problem‐solving style rather than problem‐solving ability …”
Section: Discussionmentioning
confidence: 98%
“…Patients in these studies were recruited from community advertising and research databases rather than gastroenterology clinic. A separate study that examined cognition in just IBS sufferers, found no difference in intelligence scores compared to healthy volunteers, but observed an association with a concept called constructive thinking which reflects problem‐solving style rather than problem‐solving ability …”
Section: Discussionmentioning
confidence: 98%
“…In particular, the 'cognitive model' of depression/anxiety is built on the proposition that information processing plays a key role in the way that human experiences are interpreted, evaluated, and categorized, from which emerges a personal 'schema' of one's representation of the world (55). In this model, recurring patterns of attentional bias towards negative sensations can promote negative schemas that perpetuate a maladaptive emotional state, characterized by deficits in emotional and behavioral coping, promoting depression and anxiety (56,57). Cognitive behavioural therapy has demonstrated long-lasting improvement of IBS symptoms (58,59).…”
Section: Gidd Are Associated With Changes In Cognitionmentioning
confidence: 99%
“…It is noted that the items were scored on a five-point scale, ranging from seldom to often. CTI provides a global measure of constructive thinking and includes six subscales (Emotional coping, Behavioral coping, Personal superstitious thinking, Categorical thinking, Esoteric thinking, and Naive optimism) (Rey et al, 2009). This test has been adapted and validated for use in the Greek population by Stalikas & Roussi (2016).…”
Section: Research Toolsmentioning
confidence: 99%